Effect of brown adipose tissue activation on myocardial fluorine-18-fluorodeoxyglucose uptake - Alenezi, Saud A.; Dannoon, Shorouk F.; Alnafisi, Naheel S.; Asa'ad, Saqr M.; Osman, Medhat M.; Elgazzar, Abdelhamid H. (World Journal of Nuclear Medicine, 2020)
The aim of this study is to investigate the relationship between brown adipose tissue (BAT) activation and myocardial fluorine-18-fluorodeoxyglucose ([18F] FDG) uptake in terms of intensity and patterns. The patients were divided into two groups as follows: BAT and control groups. The BAT group consists of 34 cases that showed BAT uptake. The control group, with no BAT uptake, included 68 patients who were matched for body mass index, gender, and season. The scans were retrospectively reviewed by two nuclear medicine physicians who visually evaluated the intensity of myocardial [18F] FDG uptake. The myocardial [18F] FDG uptake was visually classified into the following three patterns: diffuse, heterogeneous, and focal. The regions of activated BAT distribution were noted. The mean myocardial [18F] FDG uptake was 2.50 ± 0.75 for the BAT group and 2.13 ± 0.88 for the control group with a statistically significant difference (P = 0.031). The myocardial [18F] FDG uptake pattern was similar in the BAT and control groups with the diffuse pattern being the most common, followed by the heterogeneous and less commonly focal. In the BAT group, the anatomical distribution of BAT was mainly in supraclavicular, paravertebral, and axillary and to a lesser extent in cervical regions. BAT group had a significantly higher intensity of [18F] FDG myocardial uptake compared to that of the control group. The presence of activated BAT did not affect the pattern of myocardial uptake. Knowledge of these findings may help in understanding the variability of myocardial [18F] FDG uptake and consequently in avoiding misinterpretation of cardiac findings in positron-emission tomography/computed tomography studies.
Keywords: Activated brown adipose fat; fluorine-18-fluorodeoxyglucose; myocardial uptake